Sensors: Controllable Configuration of Sensing Band in a Pressure Sensor by Lenticular Pattern Deformation on Designated Electrodes (Adv. Mater. 36/2019). Issue 36 (3rd September 2019) - Jeong, Chanho; Lee, Ju Seung; Park, Byeonghak; Hong, Chang Seob; Kim, Jong Uk; Kim, Tae‐il
Abstract : Film‐type pressure sensors with response characteristics that are fully controllable are presented by Tae‐il Kim and co‐workers in article number 1902689, the sensors have unique properties, including linearity over a broad range of pressure, on/off switching, and low‐pressureband and high‐pressure‐band sensors. Using these sensors, any signal characteristics would be designed without any signal process.